Removal of Dyes from Synthetic Wastewater by Agriculturalwaste - Al-Najar, Jenan A. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Adsorption is one of the most important technologies for the treatment of polluted water from dyes. Theaim of this study is to use a low-cost adsorbent for this purpose. A novel and economical adsorbent was used to remove methyl violet dye (MV) from aqueous solutions. This adsorbent was prepared from bean peel, which is an agricultural waste. Batch adsorption experiments were conducted to study the ability of the bean peel adsorbent (BPA) to remove the methyl violet (MV) dye. The effects of different variables, such as weight of the adsorbent, pH of the MV solution, initial concentration of MV, contact time and temperature, on the adsorption behaviour were studied. It was found experimentally that the time required to achieve equilibrium was 120 min for all dye concentrations (10-50 mg/l). The BPA was characterised using Fourier transform infrared (FTIR)before and after adsorption of the MV dye. Langmuir, Freundlich and Temkin isotherm models were used to analyse the experimental isotherm data. The Freundlich isotherm gives a better fit than the other isotherm models. The adsorption kinetic data were tested using pseudo-first-order and pseudo–second-order models. Additionally, the intraparticle diffusion model was used to investigate the mechanism of the adsorption process. It was found that boundary layer diffusion (external mass transfer) is the rate-determining step. The thermodynamic parameters, including ΔH, ΔS and ΔG, were investigated at different temperatures (298, 313 and 323 K) and concentrations (5, 10, 20 and 30 mg/l) to understand the nature of the adsorption process. The thermodynamic study indicates that the adsorption of MV dye onto BPA is physical, exothermic and spontaneous in nature.